2017
DOI: 10.1159/000481560
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125a Regulates Cell Proliferation Via Directly Targeting E2F2 in Osteosarcoma

Abstract: Background/Aims: Increasing evidence has shown that miR-125a plays important role in human cancer progression. However, little is known about the function of miR-125a in osteosarcoma. Methods: The expression of miR-125a in osteosarcoma tissues and cell lines were examined by qRT-PCR. The biological role of miR-125a in osteosarcoma cell proliferation was examined in vitro. The targets of miR-125a were identified by a dual-luciferase reporter assay. Results: The results showed that the expression of miR-125a exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
(33 reference statements)
3
18
0
Order By: Relevance
“…It has been demonstrated that miRNAs are aberrantly expressed in various cancers such as lung cancer, liver cancer, and gastric cancer . MicroRNA‐125a (MiR‐125a), located on chromosome 19q13, is a member of the miR‐125 family and has been reported as a potential tumor suppressor in multiple cancers by targeting different genes, such as osteosarcoma, ovarian cancer, breast cancer, lung cancer, and glioma . However, little is known about the expression profile and functional roles of miR‐125a in RCC.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs are aberrantly expressed in various cancers such as lung cancer, liver cancer, and gastric cancer . MicroRNA‐125a (MiR‐125a), located on chromosome 19q13, is a member of the miR‐125 family and has been reported as a potential tumor suppressor in multiple cancers by targeting different genes, such as osteosarcoma, ovarian cancer, breast cancer, lung cancer, and glioma . However, little is known about the expression profile and functional roles of miR‐125a in RCC.…”
Section: Introductionmentioning
confidence: 99%
“…reported that overexpressed E2F2 is closely related to poor post progression survival in ovarian cancer patients, and can be used for targeted treatment and prognosis prediction [5]. Similar results can be found in glioma [6] osteosarcoma [7], gastric cancer [8] and melanoma [9], it's not surprising that E2F2 is regarded as oncogene. However, E2F2 is a suppressor gene in clear cell renal cell carcinoma [10] and Tcell lymphoma [11].…”
Section: Introductionmentioning
confidence: 67%
“…Quan Zhou et al reported that overexpressed E2F2 is closely related to poor post progression survival in ovarian cancer patients, and can be used for targeted treatment and prognosis prediction (4). Similar results can be found in glioma (5),osteosarcoma (6), gastric cancer (7) and melanoma (8), it's not surprising that E2F2 is regarded as oncogene. However, E2F2 is a suppressor gene in clear cell renal cell carcinoma (9) and T-cell lymphoma (10).…”
Section: Introductionmentioning
confidence: 75%